Optimization of bioethanol production from yeast isolated from nypa sap using response surface methodology - Natarajan, Sharmila Dewi (2012)
Bioethanol has emerged as an alternative energy to the fossil fuel as it is produced from a renewable source and is environmental friendly. Bioethanol production from economical carbon source with a cost-effective fermentation process and the suitable microorganism with high fermentation ability are the key factors for bioethanol development. This study focused on the production of bioethanol from nypa sap which is also known as ‘nira nipah’ in Malaysia. Nypa sap is obtained from Nypa fruticans and it is rich in various types of simple sugars that can readily be fermented into ethanol by yeast. In spite of such usefulness, there is a lack of scientific reports on nypa sap for bioethanol production compared to other substrates. Thus, nypa sap was selected to investigate its potential to produce bioethanol. Besides that, selection of suitable bacteria which can withstand high concentration of sugars in nypa sap and can ferment the sugars effectively is a crucial step for a successful fermentation. Therefore, isolation of wild yeast strain from the nypa sap itself ensures the high adaptability and genetic stability of the strain during fermentation of nypa sap. Furthermore, in order to attain high ethanol production, optimum fermentation conditions for the wild strain also should be studied as the requirements of microorganism for growth and ethanol production are specific to individual species. Thus, the objectives of this study were to isolate yeast from nypa sap which is capable of producing high ethanol and optimize fermentation conditions for the production of bioethanol by the selected yeast. Six yeast strains were isolated from nypa sap and were identified as Saccharomyces cerevisiae, Candida tropicalis, Candida parapsilosis, Lachancea fermentati, Candida krusei and Kloeckera sp. using API 20C AUX kit. C. krusei and Kloeckera sp. were not selected for further experiments since they do not possess the ability to utilize sucrose which is the main sugar component in nypa sap. Ethanol fermentation was carried out in shake flasks incubated at 30ºC, 200 rpm using 50 g/l nypa sap as carbon source by the isolated S. cerevisiae, C. tropicalis, C. parapsilosis, L. fermentati and Baker’s yeast. L. fermentati produced the highest ethanol (18.7 g/l) with 74.7% of theoretical ethanol value. Thus it was selected for further optimization process. In order to attain a higher ethanol production, response surface methodology was employed using temperature, pH, substrate concentrations and fermentation time as independent variables. Fermentation was carried out in 250 ml shake flasks with agitation speed of 200 rpm. Results showed that the optimum conditions for bioethanol production were temperature of 30°C, pH 5.4, substrate concentrations of 110 g/l and fermentation time of 20 hours. The model predicted that the maximum concentration of ethanol under the optimum conditions was 46.91 g/l. The verification experiment produced 46.4 g/l of ethanol which is in close agreement with the model prediction. The knowledge obtained from this research can be used in bioethanol development by carrying out scale up of this fermentation process using the optimized condition in order to apply in industrial scale.